A REVIEW ON ARSENIC POISONING AND ITS POST-MORTEM FINDINGS - Kirti Sharma; S. R. Inchulkar; Yuvraj Kaushik (International Journal of Ayurveda and Pharma Research, 2020)
Arsenic is a grey substance, which is insoluble in water and therefore cannot be absorbed from the alimentary canal. Arsenic is absorbed through all routes mainly by skin, inhalation and GIT mucosa. Arsenic causes toxicity by combining with sulphydryl enzymes and thus interfering with cell metabolism. Locally it causes irritation of the mucous membranes and remotely depression of the nervous system. Arsenic poisoning can be homicidal, suicidal, accidental, occupational, environmental, iatrogenic or un-iatrogenic. The character of post-mortem appearances depends very largely upon the quantity taken and period which has elapsed before death. Externally the body presents dehydrated, cyanosed, sunken eyeballs jaundiced in post-mortem findings. Rigor mortis lasts longer than usual. Internally red velvet stomach, petechial hemorrhages under the endocardium of the left ventricle, patchy fatty degenerative changes with jaundice in liver, rain drop skin pigmentation and mee’s line in nails findings seen in post-mortem.